HUBUNGAN SUPERVISI DAN MOTIVASI TERHADAP TINDAKAN DALAM PENCEGAHAN INFEKSI MELALUI PENGGUNAAN APD DAN HAND HYGIENE - Titik Irawati; Tri Ratnaningsih; Ana Zakiyah (Universitas Pesantren Tinggi Darul Ulum, 2022)
Infection prevention measures still have nurses who did not implemented it, this happens because of lack of awareness of nurses in addition to lack of good supervision and low motivation in following or running sop infection prevention. The purpose of the study was to analyzed the relationship of supervision and motivation of nurses against infection prevention measures through the use of PPE and Hand Hygiene in the Covid 19 Isolation Room. Correlational analytical research design. Supervision and motivation as independent variables, actions as dependent variables. The population of all nurses of Covid-19 Isolation Room Hospital Prof. Dr. Soekandar Mojokerto as many as 32 people. The sample was taken with a total sampling technique of 32 respondents. The data was collected with questionnaire instruments and tested with coeeficient contingence tests and chi square tests. The result of the coefficient contingence test for variable supervise with APD is obtained the value of ? = 0.001. Supervision with hand hygiene obtained value ? = 0.000. While the results of the chi square motivation test with APD obtained the value of ? = 0.005 < ? = 0.05, and motivation with hand hygiene obtained the value of ? = 0.004 < ? = 0.05. The results of bivariate analysis show that H1 is accepted meaning there is a relationship between supervision and motivation with infection prevention measures through PPE and hand hygiene. The results of multivariate analysis showed the beta coefficient value for supervise is higher than the motivation of 0.304 so that the most dominant variable is the supervisory variable. The implementation of good and appropriate supervision will foster the spirit and performance of the right health workers in carrying out infection prevention. Keywords: Action, Hand hygiene, Motivation, PPE, Supervision